1996
DOI: 10.3354/dao027215
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome baculovirus (WSBV) detected in cultured and captured shrimp, crabs and other arthropods

Abstract: Whlte spot syndrome baculovirus (WSBV) has been found across ddferent shrimp species and in different Asian countries. The detection of WSBV in shrimp with white spot syndrome has already been achieved by means of l-step polymerase chain reaction (PCR). In an attempt to establish a more sensitive assay, we evaluated the effect of 2-step amplification with nested primers on the sensitivity of WSBV diagnostic PCR. The sensitivity of the 2-step amplification was 10" to 10"imes higher than that of l-step amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
376
1
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(396 citation statements)
references
References 12 publications
6
376
1
13
Order By: Relevance
“…The principle clinical sign of the affected shrimp will be white spots in the exoskeleton and epidermis [1]. This virus can cause 100% mortalities within 3e10 days of the onset of the above symptoms .The WSSV has a wide host range and it has been observed not only in shrimps but also in crabs and other arthropods such as copepods, insects and pest prawns [2].…”
Section: Introductionmentioning
confidence: 99%
“…The principle clinical sign of the affected shrimp will be white spots in the exoskeleton and epidermis [1]. This virus can cause 100% mortalities within 3e10 days of the onset of the above symptoms .The WSSV has a wide host range and it has been observed not only in shrimps but also in crabs and other arthropods such as copepods, insects and pest prawns [2].…”
Section: Introductionmentioning
confidence: 99%
“…On histological analysis and in situ hybridization with WSSV-specific gene probes, it was determined that the animals were infected with an agent that appeared to be identical or very similar to WSSV. During this same time, Lo et al (1996) identified WSSV, using DNA amplification techniques, in cultured and captured species of shrimps, crabs and other arthropods. WSSV is a major concern in all shrimp-growing regions of the world and the presence of the virus in wild populations of shrimp and other crustaceans has raised serious concerns about the impact of WSSV on the environment and native aquatic species.…”
Section: Introductionmentioning
confidence: 99%
“…WSSV has been found to infect a variety of wild and cultured crustaceans and arthropods and is considered a major pathogen of Litopenaeus vannamei, that is, primary farm-raised shrimp [3][4][5][6]. Thus, WSD has been listed as a notifiable disease by the World Organization of Animal Health (Office International des Epizooties, OIE) since 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, WSD has been listed as a notifiable disease by the World Organization of Animal Health (Office International des Epizooties, OIE) since 1997. The OIE Manual of Diagnostic Tests for Aquatic Animals [7] provides a standardized approach for the diagnosis of the diseases listed in the aquatic code, and the nested polymerase chain reaction (PCR) is considered the standard for detecting WSSV [4]. According to the protocol, in the first-step PCR, 1,447 bp of the WSSV SalI DNA fragment is amplified with the WSSV 146F1 and R1 primer set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation